Determinants of homonegativity in Europe - Štulhofer, Aleksandar (Array, 2009)
This paper analyzes macro-determinants of negative attitudes toward homosexuality in 31 European societies. Using the European Values Survey 1999/2000, carried out on national probability samples, we tested the effects of tradition, modernization, and postmodernization on homonegativity. According to the findings, social distance toward homosexual persons was predicted by the Eastern Orthodox religion, a greater degree of urbanization, economic development and immigration. Disapproval of homosexuality was found associated with economic development and urbanization, while immigration had borderline significance. Although the analyses pointed to the central role of the modernization processes in increasing social acceptance of homosexuality in European societies, persisting religious traditions and more recent immigration waves limit the effect of modernization.